The mediation of sustainability : The United Nations sustainable development goals, social movements and public discourse / edited by Ben Harbisher. - Harbisher, Ben (Protest, media and culture., 2023)
This text examines the ways in which the United Nations' Sustainability Development Goals initiatives have been disseminated and legitimised by mainstream media, in government discourse and by NGO's, charitable organisations, and campaign groups.